Selecting The Suitable Sites For Wastewater Treatment Plants Using the Fuzzy Analytical Hierarchy Process (FAHP) - عوض, عادل; شليحة, رشا (Latakia University Journal -Engineering Sciences Series, 2020)
Selection of Sites for wastewater treatment plants depends on many factors and restrictions. Decision-makers take into account existing alternatives that have different specifications and characteristics and the final work is to choose the best. This process is complex because it requires a lot of data from different environmental, social and economical fields. The Fuzzy AHP method, which integrates Analytical Hierarchy Process (AHP) and fuzzy logic, as a Multi-Criteria Decision Making (MCDM) technique providing an effective scientific tool that assists and supports decision-making and allows us to determine the relative importance of the criteria taken into account. This paper presents a theoretical review of FAHP, and a numerical application of this method in selecting Suitable Sites for wastewater treatment plants using a single decision maker.